Information flow model and service flow calculation of electric power backbone communication network - Ziyan ZHAO; Jianhui FAN; Xin JIN; Dawei ZHANG; Yang LIU; Li MA; Xiaoying ZOU (Dianxin kexue)
Electric power backbone communication network service analysis and service flow calculation is the most important aspect for network plan and optimization.According to the smart grid service carried on backbone commu-nication network,the basic service model and service flow calculation method was carried out for dedicated circuit service and IP service.Based on the requirement of the “13thFive-Year” plan,the typical power system production and management information service model were carried out and the every service data flow could be calculated.The service models and service data flow calculation method were used in the “13thFive-Year” plan communication net-work plan of state grid.